THE USE OF BLOG AS A MEDIUM TO IMPROVE STUDENTS` SKILL IN WRITING HORTATORY EXPOSITION A Classroom Action Research at the Eleventh Grade Students of SMAN 12 Semarang (ELT Forum: Journal of English Language Teaching, 2013)
The purposes of this study are to investigate students’ problems in writing hortatory exposition, to explain why students have problems in writing hortatory exposition, and to find out how well does blog contribute in improving students’ mastery of writing hortatory exposition In constructing this study, the writer collected data using a classroom action research, which was carried out through four activities. The activities consisted of planning, acting, observing and reflecting. The subjects of this study were 37 students of year eleven of SMA NEGERI 12 SEMARANG in the academic year of 2011/2012. The action was done through teaching learning process. All of the teaching learning processes were presented by the help of blog.The data was analyzed qualitatively, to find the answers. Based on the data analysis from each activity, it can be seen that the students’ problems in writing hortatory exposition text were the difficulty in drawing contents, organizing text, using the language and vocabulary, and mastering the mechanics. They were caused by the lack of students’ attention, enthusiasm, activeness in asking answering questions and activeness in doing the task given by the teacher. It was found that there was a significant difference of the students’ skill in writing hortatory exposition from the pre-test, first cycle and second cycle. After the treatments, the students’ achievement in writing hortatory exposition text was improved. Therefore, using blog as a medium was effective to improve the students’ writing skill in hortatory exposition text and very beneficial for the students in order to facilitate them in learning English.To explore the advantages of using blog in teaching learning process, in the future study, not only the teachers, but also the students are also recommended to possess blog accounts. By possessing their own blog accounts, students are supposed to compose the blog posts and explore the references of their writings by themselves. It also abridges the students to share their writings and testimonials to the others’ blogs. In this way, the frequency of the communication practice and word building gradually increases that is expected to be able to improve students’ writing skill, especially in hortatory exposition text, and generally in all other text types.